2015
DOI: 10.5455/ijmsph.2015.19012015129
|View full text |Cite
|
Sign up to set email alerts
|

A psychotropic drug use study among depression patients attending private psychiatric practitioners of Dehradun, Uttarakhand

Abstract: Background: Drug use studies are beneficial in clinical practice for rational prescribing of drugs and helpful for minimizing the medication errors. Aims and Objectives:The present study investigates the prescribing pattern of various antidepressants among private practitioners of Dehradun, Uttarakhand. Materials and Methods:A retrospective observational study was carried out in a private psychiatric unit at Dehradun. A total of 196 prescriptions were analyzed using World Health Organization drug use indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Atypical antipsychotics are now rated as first-line agents because of their low propensity to cause Extrapyramidal side effects, Efficacy against refractory cases, better tolerance, low relapse rate, and safer adverse effect profile. 6 Olanzapine and Risperidone were the most commonly prescribed atypical antipsychotics, which is consistent with previous studies. Almost all prescribed antipsychotic drugs were second generation antipsychotics, Risperidone followed by Olanzapine and Quetiapine.…”
Section: Discussionsupporting
confidence: 91%
“…Atypical antipsychotics are now rated as first-line agents because of their low propensity to cause Extrapyramidal side effects, Efficacy against refractory cases, better tolerance, low relapse rate, and safer adverse effect profile. 6 Olanzapine and Risperidone were the most commonly prescribed atypical antipsychotics, which is consistent with previous studies. Almost all prescribed antipsychotic drugs were second generation antipsychotics, Risperidone followed by Olanzapine and Quetiapine.…”
Section: Discussionsupporting
confidence: 91%
“…Trihexyphenidyl was the most common anticholinergic prescribed. 10 Grohmann et al in their study analyse data on drug use in 1995 and 2001 assessed at two reference days per year and per hospital within the drug safety program AMSP were compared for 10 hospitals found that atypical neuroleptics (NL) were used in 59.9% of patients on NLs in 2001 (16.7% in 1995), most frequently olanzapine, risperidone, clozapine, and quetiapine, in this order. 39% of patients still received typical NLs in antipsychotic indication (77.1% in 1995), and 30.8% received typical hypnosedative NLs (38.1% in 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Which is contradictory to earlier report such that alprazolam was the most commonly prescribed benzodiazepine followed by lorazepam. 16 Among Antidepressants, the most commonly prescribed drugs were Desvenlafaxine (12) & Mirtazapine (12) followed by Amitriptyline (9) & Nortriptyline (9). Among Antipsychotics, the most commonly prescribed drugs include Olanzapine (25) and Risperidone (15).…”
Section: Discussionmentioning
confidence: 99%